Increased Ammonium Assimilation Activity in the Scleractinian Coral Pocillopora damicornis but Not Its Symbiont After Acute Heat Stress - Tang, Jia; Ni, Xingzhen; Wen, Jianqing; Wang, Lingui; Luo, Jian; Zhou, Zhi (Frontiers in Marine Science, 2020)
Ammonium is the main nitrogen resources for scleractinian coral-Symbiodiniaceae symbiotic association, and there is urgent need to investigate the involvement of ammonium assimilation in the heat acclimation of the symbiotic association to heat stress. In the present study, symbiont density and chlorophyll content, as well as redox and ammonium assimilation enzyme activities in two symbiotic partners of the scleractinian coral Pocillopora damicornis were firstly investigated after acute heat stress (32 °C). Symbiont density and chlorophyll content decreased significantly at 24 h (1.81×105 cell cm-2, p < 0.05) and 36 h (23.25 pg cell-1, p < 0.05) after heat stress, respectively. We observed significant activity increases of coral nitric oxide synthase, superoxide dismutase and catalase, and symbiont superoxide dismutase after heat stress, but no alterations in the activities of symbiont nitric oxide synthase and catalase during the whole experiment period. The activities of coral glutamine synthetase and glutamine oxoglutarate aminotransferase began to increase significantly at 24 h, and reached the peak at 36 h after heat stress. As for glutamate dehydrogenase activity, a significant increase was observed only at 36 h after heat stress. The activities of symbiont glutamine synthetase and glutamine oxoglutarate aminotransferase did not change significantly after heat stress. Secondly, symbiont density, chlorophyll content, apoptosis rate, coral total antioxidant capacity, and caspase3 activation level were determined after glufosinate (glutamine synthetase inhibitor) treatment. Symbiont density decreased significantly at 6 h (1.25×106 cell cm-2, p < 0.05) after glufosinate treatment, and symbiont chlorophyll content also decreased significantly during 12-24 h after glufosinate treatment, with the lowest level at 12 h (16.69 pg cell-1, p < 0.05). Furthermore, the coral total antioxidant capacity and caspase3 activation level both increased significantly at 12 h (0.57 U mg-1, 2.08-fold, p < 0.05) after glufosinate treatment, while no significant change was observed for the symbiont apoptosis rate. These results suggest that the ammonium assimilation activity in the coral host P. damicornis, not its symbiont, was induced by acute heat stress, which might contribute to the acclimatization of the symbiotic association to high temperature through regulating coral antioxidant capacity and apoptosis.